2016
DOI: 10.33151/ajp.13.1.514
|View full text |Cite
|
Sign up to set email alerts
|

Violence against Paramedics – When Will it Stop?

Abstract: This editorial looks at the acts of violence against paramedics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…Additional to contributions to the HRM field, our findings support growing evidence paramedics in Australia and overseas are at very high risk of physical, verbal, and sexual assault (Boyle & Wallis, 2016;van der Velden et al, 2016). Our article responds to calls for deeper understanding and qualitative research on situational risk factors for violence against paramedics and similar occupational groups (Pourshaikhian et al, 2016;Wongtongkam, 2017).…”
Section: Theoretical Implicationssupporting
confidence: 84%
See 3 more Smart Citations
“…Additional to contributions to the HRM field, our findings support growing evidence paramedics in Australia and overseas are at very high risk of physical, verbal, and sexual assault (Boyle & Wallis, 2016;van der Velden et al, 2016). Our article responds to calls for deeper understanding and qualitative research on situational risk factors for violence against paramedics and similar occupational groups (Pourshaikhian et al, 2016;Wongtongkam, 2017).…”
Section: Theoretical Implicationssupporting
confidence: 84%
“…Existence of wellresourced and quality systems assist employees to process and rehabilitate from violence and trauma (Kellner, Townsend, Loudoun, Dao-Tran, & Wilkinson, 2019a;Kellner et al, 2019b), or in the case of de-escalation training, potentially reduce the incidence of assault. As noted by others (Boyle & Wallis, 2016), inconsistencies exist in training (resilience and de-escalation) for paramedics and students during tertiary study. Interviewees acknowledge the value of training prior to workforce entry, particularly given identification of age and limited experience as a risk factor.…”
Section: Practical and Policy Implicationsmentioning
confidence: 94%
See 2 more Smart Citations
“…Sources of such stress include high acuity patients that decompensate quickly, performance of highintensity procedures, a lack of personal time, and a disruption of social support (LeBlanc, 2009). Paramedics are regularly subjected to emotionally challenging work (Williams), violence (Bigham et al, 2014;Boyle and Wallis, 2016) occupational injury (Maguire et al, 2014), poor physical health status (MacQuarrie et al, 2018;Sheridan, 2019), and the effects of shift-work (Patterson et al, 2012). In addition, operational experiences such as attending hoax calls, missing meal breaks, and interacting with the public appear to influence psychological health, anxiety and stress in paramedics (Brough, 2004) The literature on stress and performance is ambiguous and conflicting; some studies demonstrate no impact or even improvement of task performance, while other studies have demonstrated a negative impact on performance while stressed.…”
Section: Introductionmentioning
confidence: 99%